Cluster Preface: Catalysis Using Sustainable Metals – Part II - Gaunt, Matthew J.; Chow, Hak-Fun; Rovis, Tomislav (Synlett, 2015)
The discovery of new catalytic reactions involving the use of abundant, inexpensive, and sustainable metal complexes has enjoyed a resurgence of activities in recent years. This Cluster, the second of a two-part series, continues the update of this important field, communicating a variety of approaches that address this important challenge.
Keywords: sustainable metal; catalysis; cycloaddition; aminoxylation; dimerization; quinolone; S-arylation; biomass conversion